EVALUATION OF FUNCTIONAL INTEGRITY OF NEUROMUSCULAR JUNCTION BY SINGLE FİBER ELECTROMYOGRAPHY İN HEMIPLEGIC PA TIENTS - Metin Karataş; Seyhan Sözay; Meral Bayramoğlu; Rıdvan Özker (Archives of Rheumatology, 2000)
Muscle wasting in hemiplegia and degenerative changes in lower motor neurons contrlateral to cerebral lesions have been well documented. But the electrophysiological features and pathogenesis of hemiplegic muscle atrophy remains unexplained. A transneuronal degeneration of corticospinal fibres have been suggested to explain these features. İn the present study, the functional integrity of neuromuscular transmission was assessed by stimulated single fibre electromyography with axonal microstimulation (stim-SFEMG) in Extansor Digitorum Communis (EDC) muscle contrlateral to cerebral lesions of stroke patients. Neuromuscular jitter was measured in 24 hemiplegic patients with normal peripheral nere conduction studies and in whom the disease duration from the onset of stroke until the examination was longer than 6 months. Although mean of mean jitter values in whole group was vvithin normal limits, there were incresed jitter values for at least 2 individual muscle fiber which supports a neuromuscular transmission disorder in 6 patients. There was no relationship betvveen motor recovery stages of hemiplegic upper extremity and disease duration with neuromuscular jitter values, but mean neuromuscular jitter values was negatively correlated with the degree of finger and vvrist extensor muscle tonus. Such changes in neuromuscular transmission may be related to transsynaptic degeneration of lower motor neurons as a consequences of the interruption of corticospinal tract. These findings suggested that neuromuscular transmission disorder in some of the hemiplegic patients can be demonstrated not only in the earlier phases of denervation-reinervation process, but also in long standing cases.